A Decrease of Brain MicroRNA-122 Level Is an Early Marker of Cerebrovascular Disease in the Stroke-Prone Spontaneously Hypertensive Rat. (18th June 2017) - Stanzione, Rosita; Bianchi, Franca; Cotugno, Maria; Marchitti, Simona; Forte, Maurizio; Busceti, Carla; Ryskalin, Larisa; Fornai, Francesco; Volpe, Massimo; Rubattu, Speranza
Abstract : Based on preliminary evidence that highlights microRNA-122 as a contributing factor to stroke pathogenesis, we aimed at assessing its expression level, along with the presence of early signs of cerebrovascular disease, in the brain of stroke-prone spontaneously hypertensive rat (SHRSP), a suitable model of human disease that accelerates stroke occurrence under a high sodium/low potassium (Japanese-style) diet (JD). After one month of JD, before stroke occurrence, brain microRNA-122 level was significantly decreased in SHRSP as compared to the stroke-resistant SHR (SHRSR). At this time, levels of markers of oxidative stress and inflammation, as well as of endothelial integrity and function, apoptosis and necrosis were differently modulated in the brains of JD-fed SHRSP as compared to SHRSR, pointing to a significant activation of all deleterious mechanisms underlying subsequent stroke development in SHRSP. We also showed that miR-122 improved survival of rat endothelial cerebral cells upon stress stimuli (excess NaCl, hydrogen peroxide). Our data suggest that a decrease of brain microRNA-122 level is deleterious and can be considered as an early marker of stroke in the SHRSP. Understanding the mechanisms by which microRNA-122 protects vascular cells from stress stimuli may provide a useful approach to improve preventive and treatment strategies against stroke.